The Thoughts of Muslim Philosopher Al Thusi on Islamic Philosophy - Nendah Mutmainah; Rabiatul Adawiyah; Fuspa Anggraeni; Wildan Muhammad taqiy; Fetty Nur Fatimah (Bibliotheca: Journal of Philosophy, 2025)
Until now, the dynamics of thought in the Islamic filosofi world continues to grow. With an attitude that raises, is tolerant, and accommodative of Muslims to hegemony of thought as well as foreign civilization, love of knowledge, academic culture, the work of Muslim scholars in government as well as social institutions, development of schools by prioritizing ratios as well as freedom of thought, expanding the prosperity of various countries Islam, the problems faced by Islam all the time that increasingly require solutions are growing rapidly. In fact, it is possible to have a doctrine that makes reason high which may be a source of truth as well as knowledge. As for the Alquran and hadith, it is not uncommon to issue the importance of reasoning, research and thought. From this doctrine, philosophy was born in Islamic countries. With the existence of several philosophers who contributed to Islamic countries in the development of Western intellectual traditions, it turns out that many Western scientists have recognized them. Then came the philosophers in the Islamic world both in the East and West. In this paper, the character Nasiruddin At-Tusi is studied as a "versatile scientist" or multitalented, a Muslim scientist from Persia who has made developments in fields of science such as Astronomy, Chemistry, Biology, Philosophy, Mathematics, Medicine, as well as Religion. Islamic. The essence of the problem in this finding is how the history of Islamic thought and civilization according to Nasiruddin At-Tusi. This research uses qualitative research, so this research is a type of literature review. That is the method of collecting library data, reading and taking notes as well as managing research materials. Sources of data for this research were sought from various literatures that describe historical thought and Islamic civilization. The results of this study try to describe the historical thought and civilization of Nasiruddin At-Tusi reform in the Islamic world.